Neural networks to model COVID-19 dynamics and allocate healthcare resources - Abdullah Ali H. Ahmadini; Yashpal Singh Raghav; Ali M. Mahnashi; Khalid Ul Islam Rather; Irfan Ali (Scientific Reports)
Abstract This study presents a neural network-based framework for COVID-19 transmission prediction and healthcare resource optimization. The model achieves high prediction accuracy by integrating epidemiological, mobility, vaccination, and environmental data and enables dynamic resource allocation. The results demonstrate significant improvements in forecasting performance and healthcare preparedness compared to traditional models. This work enhances decision-making in pandemic management by leveraging machine learning for real-time operational efficiency.